ANALYSIS OF REVIEW RATING DYNAMICS FOR NICHE AND MAINSTREAM BRANDS: A CASE FROM THE INDONESIAN MARKET - Zaenal Aripin; Lili Adi Wibowo; Faisal Matriadi (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
Consumer review ratings have become an increasingly important factor in shaping brand perception in the modern marketplace. However, little research has focused on differences in review ratings between niche and mainstream brands, especially in the context of the emerging Indonesian market. This research aims to analyze the dynamics of review ratings for niche and mainstream brands in the Indonesian market, with a focus on the factors that influence review ratings, the differences between niche and mainstream brands, and the strategic implications for brands. The research method used in this study is a qualitative analysis of consumer reviews found on online platforms, such as specialized review sites, social media, and discussion forums. Data was also collected from interviews with consumers and brand owners to gain deeper insight into the factors that influence review ratings. The research results show that there are significant differences in review ratings between niche and mainstream brands in the Indonesian market. Consumers tend to give more positive reviews to niche brands, because they feel more connected to the brand and perceive their experience as more authentic. Factors such as product quality, price, customer satisfaction, and brand image also play an important role in assessing consumer reviews.